Kangaroo Mother Care and Swaddling Methods In Low Born Weight Babies In Community Settings: A Systematic Review - S. Tauriana; Joni Haryanto; Retnayu Pradanie (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Infants born with low birth weight or LBW are very susceptible to hypothermia due to the thin fat reserves under the skin and immature heat regulating centers in the brain. The search for articles consisted of five databases, namely Scopus, Science Direct, PubMed, Garuda, and Proquest. Analysis of 25 articles on kangaroo mother care and self-care showed that kangaroo mother care can keep the baby's body temperature stable and reduce the risk of hypothermia in newborns with low weight and make it easier for the baby to breastfeed. This systematic review shows that the kangaroo mother care method has a more significant impact on baby weight gain and the stability of the baby's body temperature by maintaining skin to skin contact between mother and baby for later implementation in the community. This method is more effective than the swaddling method. Keyword: Kangaroo Mother Care; Swaddling; Low Birth Weight; Community